Phenotypic and genotypic features of a large kindred with a germline AIP variant. (18th May 2020) - Dal, Jakob; Nielsen, Eigil H.; Klose, Marianne; Feldt‐Rasmussen, Ulla; Andersen, Marianne; Vang, Søren; Korbonits, Márta; Jørgensen, Jens Otto L.
Abstract: Context: Acromegaly is usually a sporadic disease, but familial cases occur. Mutations in the aryl hydrocarbon receptor‐interacting protein ( AIP ) gene are associated with familial pituitary adenoma predisposition. However, the pathogenicity of some AIP variants remains unclear and additional unknown genes may be involved. Objective: To explore the phenotype and genotype of a large kindred carrying the p.R304Q AIP variant. Methods: The family comprised 52 family members at risk of carrying the p.R304Q AIP variant including a case with gigantism and one with acromegaly and several family members with acromegalic features. Nine family members (three trios) underwent exome sequencing to identify putative pathogenic variants. Results: We identified 31 p.R304Q carriers, and based on two cases with somatotropinomas, the disease penetrance was 6%. We observed physical signs of acromegaly in several family members, which were independent of AIP status. Serum insulin‐like growth factor‐I (IGF‐I) levels in all family members were above the mean for age and sex (IGF‐I SDS: +0.6 [CI95% +0.4‐0.9], P  < .01). Exome analysis identified two candidate genes: PDE11A, known to be associated with the development of adrenal tumours, and ALG14 . Ten asymptomatic p.R304Q family members (age >50 years) were screened for the PDE11A and ALG14 variant; both variants were present in five of ten persons. Conclusions: This large family adds new information on the p.R304Q AIP variant, and data suggest two new candidate genes could be associated with growth hormone excess.